Pelatihan dan Pembuatan Alat Penjernih Air Sederhana di Rumah Yatim dan Pesantren Ruhama - Ahsonul Anam; Gadang Priyotomo; Budi Kaliwanto; Rifki Eka Ramdan; Yopi Andreyanto; Maulana Akhsan; Dhian Ayu Puspitasari; Septiansyah Amelian Saputra (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
The weight of an adult's body consists of approximately 55-60 percent water. Water for living things is very important. Water is needed for survival so that the body works optimally. This paper is a writing about Community Service (PKM) activities with PKM partners, namely Rumah Yatim and Pesantren Ruhama, which are facilitator and mediator institutions to share with orphans, orphans, poor and neglected children from various regions in pursuing a better future. PKM partner students who come from various regions sometimes find it very difficult to get clean/clear water sources. Sometimes the surface water is very cloudy, making it uncomfortable when used for household purposes. Simply put, water purification functions to reduce turbidity, slightly eliminate or reduce odors, but has not been able to reduce the level of pollutants in it so that it is suitable for its final use, for example for consumption purposes such as drinking, cooking and others. By holding PKM at the Ruhama Orphanage and Islamic Boarding School, it will provide knowledge